Evaluating University Students’ Perceptions of Artificial Intelligence Integration in Islamic Civilization History Learning and Its Relation to Academic Adab - Muriyanto Muriyanto; Ngatmin Abbas; M. Fatchurrohman; Dudi Budi Astoko (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This study analyzes the integration of Artificial Intelligence (AI) into Islamic Civilization History learning and its implications for strengthening students’ academic adab. The study employed a quantitative survey involving 80 students enrolled in the Islamic Civilization History course. Data were collected through an online questionnaire and analyzed using frequencies and percentages. The findings show that students perceive AI as a supportive learning tool that helps them understand course materials, summarize content, complete assignments efficiently, and develop flexible and independent learning practices. Importantly, AI use did not automatically weaken academic adab because students positioned it as an auxiliary tool rather than a substitute for intellectual effort, lecturer guidance, and personal responsibility. Most respondents maintained academic honesty, verified AI-generated information, avoided total dependence, respected lecturers as the primary instructional authority, and used AI with ethical awareness. These findings suggest that academic adab is shaped not merely by access to technology, but by students’ critical literacy, ethical orientation, and understanding of scholarly responsibility. The study proposes an ideal integration model based on four principles: pedagogical guidance, critical verification, transparent attribution, and reflective use. Therefore, AI should be integrated into Islamic Civilization History learning through academic rules, lecturer supervision, source checking, and assignments requiring interpretation, argumentation, and reflection. Such integration enables AI to enhance learning without reducing intellectual independence, historical reasoning, or academic integrity.